Promoting Luminor Hotel Pahlawan, Sidoarjo to Its Target Market Using a Marketing Booklet - Asti Kusumaningtyas (Kata Kita: Journal of Language, Literature, and Teaching, 2020)
This is a creative thesis report on a problem that Luminor Hotel Pahlawan, Sidoarjo has. The three-star hotel located in Sidoarjo is believed to have ineffective marketing tools. Their prospects tend to ask for further information such as pictures and detail description of the facilities. Flyers that the salespeople usually give to the prospects are less informative. Thus, in order to introduce the product to the representatives of the prospects a marketing booklet is needed. Marketing booklet which has more spaces to deliver information can help the salespeople to answer customers’ needs. To persuade the readers, Luminor Hotel Pahlawan, Sidoarjo’s Unique Strength Points (USP) will be emphasized in the marketing booklet contents.Keywords: marketing tool, marketing booklet, unique selling point, target market.